AUDREY TURNER’S CONFLICTS AND DEFENSE MECHANISMS IN KINSELLA’S 'FINDING AUDREY' - M. Aprianto Budie Nugroho; Sely Viladinia (UIN Raden Mas Said Surakarta, 2018)
A story becomes interesting because of the existence of the characters’ conflicts. This research objectives were to investigate the conflicts and defense mechanisms in Audrey Turner, the main character of Finding Audrey novel written by Sophie Kinsella. This research was conducted in qualitative method by using narrative research design. The collected data were identified, categorized, and analyzed based on literature and psychology perspectives of Islam’s (2016) theory and defense mechanisms by Cramer (2006). The findings show that person vs him/herself as the internal conflict is found 52 times (67.5%). The first external conflict found is person vs person which appears 23 times (29.9%) It is followed by person vs society and person vs nature conflicts, each of which appears once only (1.3%). Three kinds of defense mechanisms are found as well. The denial defense mechanisms are found 72 times (54.1%) whereas projection and identification are each found as many as 48 times (36.1%) and 13 times (9.8%). It means that Audrey, as the main character, mostly faces conflicts against her own self and feels of fears affected from her anxiety disorder and people around her. To deal with her conflicts, Audrey mostly uses denial as a defense mechanism to protect herself.